Emergence of Nanomedicine as Cancer Targeted Magic Bullets: Recent Development and Need to Address the Toxicity Apprehension - Rahman, Mahfoozur; Zaki Ahmad, Mohammad; Kazmi, Imran; Akhter, Sohail; Afzal, Muhammad; Gupta, Gaurav; Ranjan Sinha, Vivek (Current Drug Discovery Technologies, 2012)
Multi drug resistance and non specific targeting is a major problem with conventional therapy. To overcome this problem, nanoparticles (NPs) have emerged as an important tool to deliver conventional drugs, recombinant proteins, vaccines and more recently, nucleotides. NPs modify the drug release pattern, absorption, distribution, metabolism, excretion (ADME) and therapeutic response. This review focuses on the potential of nanotechnology in cancer and discusses the different nanoparticulate drug-delivery systems including quantum dot, iron oxide nanoparticles, gold nanoparticles, carbon nanotubes, silica nanoparticles, dendrimer, graphene and polymeric nanoparticles with their applications in therapeutics, diagnostics, and imaging pattern. Further, the recent development and progress of theranostic nanoparticles in the treatment of cancer and toxicity associated with nanoparticles is also covered here.
Keywords: physicochemical properties